Plasma tRF-1:29-Pro-AGG-1-M6 and tRF-55:76-Tyr-GTA-1-M2 as novel diagnostic biomarkers for lung adenocarcinoma - You, Jianbin; Yang, Guoliu; Wu, Yi; Lu, Xuan; Huang, Shuyu; Chen, Qianshun; Huang, Chen; Chen, Falin; Xu, Xunyu; Chen, Liangyuan (Frontiers in Oncology, 2022)
Abstract Objective: The transfer RNA (tRNA)-derived fragments (tRFs/tiRNAs) are recognized as a novel and potential type of non-coding RNAs (ncRNAs) and several tRFs/tiRNAs signatures are associated with tumor diagnosis.This study aimed to analyze the expression profiles of plasma tRFs/tiRNAs and to clarify their diagnostic value in lung adenocarcinoma (LUAD). Methods: The differential expression profiles of plasma tRFs/tiRNAs in patients with 4 early LUAD, 4 advanced LUAD and 4 normal controls were analyzed by high-throughput sequencing technology. Then, plasma tRFs/tiRNAs were validated by quantitative real-time polymerase chain reaction (qRT-PCR) and their diagnostic efficiency was appraised by receiver operating characteristic curve (ROC). Moreover, the correlation of plasma tRF/tiRNAs with clinicopathological features were further analyzed. Ultimately, bioinformatics analysis was performed to ccharacterize the potential biological pathways induced by tRFs/tiRNAs. Results: The sequencing results revealed that altered tRFs/tiRNAs expression from plasma samples in patients with LUAD and supports their role as potential biomarkers. The validation results of qRT-PCR demonstrated that the expression level of tRF-1:29-Pro-AGG-1-M6 was down-regulated in LUAD, while the expression level of tRF-55:76-Tyr-GTA-1-M2 was up-regulated, which was consistent with the sequencing data. The AUCs of tRF-1:29-Pro-AGG-1-M6 and tRF-55:76-Tyr-GTA-1-M2 were 0.882 and 0.896, respectively, which have stupendous value in the diagnosis of LUAD. The expressions of tRF-1:29-Pro-AGG-1-M6 and tRF-55:76-Tyr-GTA-1-M2 in LUAD were obviously correlated with various clinicopathological features such as TNM stage, N stage, and the expression levels of CEA. In addition, they were significantly altered after tumor surgical resection. The results of GO and KEGG analysis indicated that tRF-1:29-Pro-AGG-1-M6 and tRF-55:76-Tyr-GTA-1-M2 were widely distributed and apparently enriched in several tumor-related signaling pathways . Conclusions: Plasma tRF-1:29-Pro-AGG-1-M6 and tRF-55:76-Tyr-GTA-1-M2 may be promising in the development of non-invasive biomarkers for LUAD diagnosis.